Effect of different remineralizing agents on the initial carious lesions - A comparative study - Mohammed Alhamed; Faisal Almalki; Ahmad Alselami; Tariq Alotaibi; Wahdan Elkwatehy (Elsevier, 2020)
Objectives: This study aimed to assess and compare the effectiveness of three different remineralizing agents (Tricalcium phosphate paste, Fluoride varnish, and Nano-hydroxyapatite gel) using the DIAGNOdent device. Material and Methods: The present clinical study was carried out on 90 initial carious lesions detected by ICDAS caries diagnostic criteria and then take the baseline record by DIAGNOdent device. The selected initial carious lesions were randomly classified into three groups according to treatment modalities (30 lesions in each group) according to remineralizing agents: group A (TCP), group B (fluoride varnish) and group C (nano-hydroxyapatite gel). The remineralizing agents were applied for four minutes once weekly for four weeks. At the fifth week, the DIAGNOdent scores of initial carious lesions were recorded to evaluate the effect of remineralizing agents. A paired t-test was used to compare between baseline date and follow up of DIAGNOdent scores. A one-way ANOVA test was used to compare DIAGNOdent scores among the three groups. Post- Hoc Tukey test was used to determine the significant difference between every two groups. Results: There were statistically significant differences among the three groups at follow up (p = 0.001). Within each group, there was a significant difference between baseline and follow up scores (p = 0.000 for the three groups). Multiple comparisons between every two groups showed a highly statistically significant difference at follow up records between nano-hydroxyapatite versus TCP and fluoride varnish on pit and fissure caries (p = 0.039 and p = 0.007 respectively) and the nano-hydroxyapatite was the best of them. Conclusion: The present study concluded that the three remineralizing agents were effective in the treatment of initial carious lesion and the most effective remineralizing agent was nano-hydroxyapatite.